Be Wary of Those Who Ask : A Randomized Experiment on the Size and Determinants of the Enumerator Effect - Di Maio, Michele; Fiala, Nathan (World Bank, Washington, DC, 2018)
During survey data collection, respondents' answers may be influenced by the behavior and characteristics of the enumerator, the so-called enumerator effect. Using a large-scale experiment in Uganda randomly pairing enumerators and respondents, the study explores for which types of questions the enumerator effect may exist. It is found that the enumerator effect is minimal in many questions, but is large for political preference questions, for which it can account for over 30 of the variation in responses. The study then explores which enumerator characteristics, and which of their combination with respondent characteristics, could account for this effect. Finally, the conclusion provides some practical suggestions on how to minimize enumerator effects, and potential bias, in various types of data collections.